TALES OF A. S. PUSHKIN - Nabijonova Umida Faxriddin qizi (Web of Journals Publishing, 2025)
The author talks about the literary tales of Alexander Pushkin. We consider all of his published stories. They cause reflections, more controversial, ambiguous evaluation. Tales of the great Russian poet waiting to be explored. We are talking about vzaimosyazi culture and literature. This connection, the author shows by examples.
Keywords: The phenomenon of culture, types of culture, national culture, literature.